Structural petrology along a transect across the Thompson Belt, Manitoba: dip slip at the western Churchill–Superior boundary - Fueten, Frank; Robin, Pierre-Yves F. (Canadian Journal of Earth Sciences, 1989)
Early Proterozoic rocks and Archean gneisses of the Thompson Belt, east of the Churchill Province – Superior Province boundary, record the history of the Hudsonian Orogeny in this area. A structural study has been undertaken along a 45 km long corridor cutting across the width of the belt.Three blocks are defined along this transect, each characterized by a specific structural style and metamorphic history, Foliation and lineation data and the analysis of kinematic indicators from these blocks show that (i) the Thompson Belt has been an area of predominantly dip-slip movement for its recognizable ductile deformation history; (ii) the sense of shear for most of that history corresponds to the Superior side moving up with respect to the Churchill side; (iii) the shearing emplaced rocks of progressively higher metamorphic grade towards the southeast, away from the Churchill–Superior boundary; and (iv) there appears to have been a period of movement at the later stages of the Hudsonian Orogeny during which the sense of movement was Churchill side up.Structural and metamorphic data support a tectonic model in which the Superior Province has been thrust over the Churchill Province, with a convergence direction approximately perpendicular to the Thompson Belt.